Research and Realization of Wireless Sensor Networks Database - Ping Liu (Institute of Advanced Engineering and Science, 2014)
As the core application of wireless sensor network technology, Data management and processing have become the research hotspot in the new database. This article studied mainly data management in wireless sensor networks, in connection with the characteristics of the data in wireless sensor networks, discussed wireless sensor network data query, integrating technology in-depth, proposed a mobile database structure based on wireless sensor network and carried out overall design and implementation for the data management system. http://dx.doi.org/10.11591/telkomnika.v12i10.5469